Framing happiness in Fahruddin Faiz’s digital sermons on the Ngaji Filsafat YouTube channel: A William A. Gamson’s perspective - Abdur Rosid; Mastur Mastur; Penny Yurisa; Shinta Maulidiyah (al-Balagh : Jurnal Dakwah dan Komunikasi, 2026)
Research on digital da’wah has tended to be descriptive and has not examined much about how narratives of happiness are discursively framed. This study aims to analyse the framing of narratives of happiness in Dr Fahruddin Faiz's digital lectures on the Ngaji Filsafat YouTube channel, using William A. Gamson's framing theory. This study uses a qualitative discourse analysis approach, drawing on lecture transcripts on the theme of happiness collected through documentation, observation, and reflective field notes. Data analysis was carried out in the stages of data condensation, data presentation, and conclusion drawing, according to Miles and Huberman. The results show that narratives of happiness are constructed through framing devices such as metaphors, key phrases, illustrative examples, and visual imagery, supported by spiritual-existential reasoning patterns. Happiness is positioned as a process of self-management and ongoing spiritual orientation. Implicatively, these findings emphasize the role of digital da’wah as a psycho-religious framework in building the psychological resilience of audiences in the contemporary digital space.